2005
DOI: 10.1038/nature03274
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging with cellular resolution reveals precise micro-architecture in visual cortex

Abstract: Neurons in the cerebral cortex are organized into anatomical columns, with ensembles of cells arranged from the surface to the white matter. Within a column, neurons often share functional properties, such as selectivity for stimulus orientation; columns with distinct properties, such as different preferred orientations, tile the cortical surface in orderly patterns. This functional architecture was discovered with the relatively sparse sampling of microelectrode recordings. Optical imaging of membrane voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

62
1,000
6
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,080 publications
(1,094 citation statements)
references
References 36 publications
62
1,000
6
1
Order By: Relevance
“…A recently developed extracellular injection technique has made it possible to load all or nearly all neurons in a 200-to 300-m region of cortex with a cell-permeant version of the calcium indicator OregonGreen BAPTA-1 (OGB-1) (13,14). This technique has been applied successfully to the study of neuronal response properties in rodent visual cortex (15)(16)(17).…”
Section: Imaging Responses In Labeled Inhibitorymentioning
confidence: 99%
“…A recently developed extracellular injection technique has made it possible to load all or nearly all neurons in a 200-to 300-m region of cortex with a cell-permeant version of the calcium indicator OregonGreen BAPTA-1 (OGB-1) (13,14). This technique has been applied successfully to the study of neuronal response properties in rodent visual cortex (15)(16)(17).…”
Section: Imaging Responses In Labeled Inhibitorymentioning
confidence: 99%
“…Ces résultats donnent également des indices sur les règles qui régissent le développement des connexions neuronales dans le cortex visuel. Dans le cortex visuel des rongeurs, les neurones ayant des sélectivités d'orientation différentes sont distribués de façon aléatoire [10] et non pas organisés en colonnes comme chez les mammifères supérieurs (chat, furet, primates, par exemple) [3,11,12]. L'arrangement apparemment aléa-toire des afférences synaptiques décrit ci-dessus pourrait donc provenir du fait que chaque neurone reçoit des afférences synaptiques de ses voisins de façon aléa-toire.…”
Section: Nouvelles Magazineunclassified
“…Recent two-photon fluorescence imaging studies have demonstrated the power of calcium measurements to characterize neuronal population behavior in exposed regions of the brain [12,13]. MRI indicators for calcium can facilitate calcium imaging of deep tissue structures.…”
Section: Indicators For Ca 2+ and Other Metal Ionsmentioning
confidence: 99%
“…The technique involves following the kinetics of a 13 C-labeled metabolite, pyruvate, by 13 C MRI ( Figure 1D). Normally, 13 C MRI is too insensitive to detect pyruvate at physiologically relevant concentrations, but here the authors used a method called dynamic nuclear polarization to boost the MRI signal from 13 C 1 -pyruvate using a specialized device [37]. Kinetics of pyruvate uptake and turnover to lactate and alanine were followed in the muscles and abdominal organs of rats and pigs.…”
Section: Probes For Metabolic Activitymentioning
confidence: 99%
See 1 more Smart Citation